2015
DOI: 10.1177/0194599815581808
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Contamination Predisposes to Complications after Neck Dissection

Abstract: Using the ACS-NSQIP data set, this study found an increased risk of surgical complications in the setting of contaminated neck dissections. These data should be used for patient risk stratification, informed consent, and to guide further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The larger the tumor size, the larger and more complex the wound. Wound exudation that contains fibrin promotes surface reepithelialization, while excessive fluid increases the dead space . It may induce surgical site infection in the surgical region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger the tumor size, the larger and more complex the wound. Wound exudation that contains fibrin promotes surface reepithelialization, while excessive fluid increases the dead space . It may induce surgical site infection in the surgical region.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue breakdown, such as flap necrosis, may result in contamination and vessel exposure in the neck area . Previous studies have shown that exacerbation of flap necrosis results in the resident flora and saliva enzymes of the mouth affecting the neck area and inducing infection and postoperative hemorrhage. A retrospective analysis on head and neck tumor surgery and reconstruction by Smith suggested that consideration of the medical situation and flap choice is important to protect the patient from complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 12 studies that fit the inclusion criteria plus the current study performed by the authors were enrolled in the systematic review (Table 3). [1][2][3]5,9,[16][17][18][19][20][21][22] Figure 2 and Table 3 show the selection process and an overview of the excluded studies. All included studies used administrative data, and all studies except the present one were performed in the United States.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Dissecting the neck in patients with oral cancer increases pathways of communication between it and the oral cavity, which heightens the probability of indigenous oral bacteria migrating to the former. In some patients, a reduction in perioperative oral ingestion can result in compromised nutrition, thus greatly increasing the risk of a postoperative surgical site infection (SSI) 6) . The purpose of this study was to investigate neck infections after neck dissection in oral cancer patients with the aims of elucidating the development of SSIs and their relationship with the results of bacterial culture.…”
Section: Introductionmentioning
confidence: 99%